SAR imaging model of low‐flying airplane target at complex maritime scene. Issue 19 (5th August 2019) - Peng, Peng; Guo, L.X.; Chen, B.; Wang, Y.J.
Abstract : In the actual scenario, the target is often located in a certain environment and the influence of the environment scattering and the scattering from the multipath interactions between the target and background environment can make the synthetic aperture radar (SAR) characteristics quite different from those of the targets in the free space. The SAR imaging of the low‐altitude target in the complex environment is not well studied yet. This study has developed an electromagnetic scattering model to illustrate the SAR characteristics of a low‐flying airplane target at the maritime scene. The results can reflect the influence of sea surface scattering and the multipath scattering effect very clear. The results can also help understanding the SAR characteristics of the low‐flying target at the practical maritime scene.